Postharvest insect infestation in maize grain stored in woven polypropylene and in hermetic bags - Ognakossan, Kukom Edoh; Tounou, A.K.; Lamboni, Y.; Hell, K. (Springer, 2012)
Maize was artificially infested with either 10 or 25 individual Prostephanus truncatus (Horn) and Sitophilus zeamais (Motschulsky) or a mixture of both, and stored in a hermetic grain bag (HGB) or a woven polypropylene bag (WPB) for 150 days. Population growth of P. truncatus and S. zeamais during storage was low in HGB, while in WPB, the insect population increased significantly with storage duration. Mortality rate during storage was significantly higher in HGB than in WPB. After 60 days of storage, the average mortality rate of 99.50% was observed in HGB infested with 25 P. truncatus, and 100% for S. zeamais at the same infestation density after 90 days of storage. Grain losses were significantly lower in HGB compared with WPB. Less than 0.5 and 6.0% losses were obtained, respectively, for S. zeamais and P. truncatus in HGB infested with 25 individual insects after 150 days of storage, whereas losses of 19.2% (infestation with S. zeamais) and 27.1% (infestation with P. truncatus) were observed in WPB. HGB seems to be resistant to the perforation of S. zeamais, but not to P. truncatus. The moisture content of maize grains stored in HGB remained practically the same during storage, compared with the levels in WPB, which reduced with storage time. WPB could be used for maize storage, protecting it against insect infestation without the need for insecticide use.